1999
DOI: 10.1007/s005340050084
|View full text |Cite
|
Sign up to set email alerts
|

Vascular anatomy of the pancreaticoduodenal region: A review

Abstract: Vascular anatomy of the pancreaticoduodenal region has been the subject of numerous studies. However, several essential areas of confusion remain in interpretation of the vascular configuration. We note and discuss three key points in relation to this confusion: (1) a missing vascular arcade, (2) a rearrangement of the arcade by collateral and/or transverse vessels, and (3) a solitary vessel without an accompanying comites vein or artery. In addition, we consider that different interpretations as well as varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 37 publications
4
44
0
4
Order By: Relevance
“…During pancreaticoduodenectomies or lymph node resection procedures, ligation of IPDA also requires special attention, because of high incidence of common trunk formation of the first jejuna and IPDA 6 . The present study emphasizes the uncommon variations in the pancreaticoduodenal artery as it was arising from the hepatic artery, so it is a rare case because as per the previous investigators only 2.7% of the cases arises from the hepatic artery.…”
Section: Resultsmentioning
confidence: 99%
“…During pancreaticoduodenectomies or lymph node resection procedures, ligation of IPDA also requires special attention, because of high incidence of common trunk formation of the first jejuna and IPDA 6 . The present study emphasizes the uncommon variations in the pancreaticoduodenal artery as it was arising from the hepatic artery, so it is a rare case because as per the previous investigators only 2.7% of the cases arises from the hepatic artery.…”
Section: Resultsmentioning
confidence: 99%
“…Lahko je desna ali leva veja SMA, izvira kot samostojna veja ali kot dve hkrati (anteriorna in posteriorna). Izvira lahko tudi iz prve strokoVni čLanek jejunalne veje SMA (60-80 %) (2,3,5,11). IPDA oskrbuje spodnji del dvanajstnika, glavo in odrastek trebušne slinavke.…”
Section: Arteria Pancreaticoduodenalis Inferior Anterior Posteriorunclassified
“…V primerih, ko IPDA ni prisotna, morajo kirurgi upoštevati neobičajni arterijski lok, da se izognejo nepotrebnim krvavitvam (12). Prav tako je potrebna velika pazljivost za IPDA zaradi nastalega skupnega debla med zgornjo jejunalno arterijo in IPDA (11).…”
Section: Arteria Pancreaticoduodenalis Inferior Anterior Posteriorunclassified
“…As lymphatics (lymph node and lymph vessels) accompany the arteries and are distributed in the surrounding neural plexuses, complete clearance of peripancreatic tissue, including lymphatics and nerve plexus, is necessary for curative resection of the tumor. [1][2][3][4] As this operation is considered a complex procedure, a surgeon is required to be well trained in this specific surgical technique and to possess sufficient anatomic knowledge.Despite a low mortality rate and improvements in perioperative care and operative management, there is still a relatively high complication rate following PD. 5,6 Several studies showed that intraoperative bleeding and red blood cell (RBC) transfusion are serious risk factors of postoperative complications in PD.…”
mentioning
confidence: 99%
“…As lymphatics (lymph node and lymph vessels) accompany the arteries and are distributed in the surrounding neural plexuses, complete clearance of peripancreatic tissue, including lymphatics and nerve plexus, is necessary for curative resection of the tumor. [1][2][3][4] As this operation is considered a complex procedure, a surgeon is required to be well trained in this specific surgical technique and to possess sufficient anatomic knowledge.…”
mentioning
confidence: 99%